The Impact of Industrial Sites on Residential Property Values - Friso de Vor; Henri L.F. de Groot (Tinbergen Institute, 2009)
Industrial sites cause several negative externalities, such as traffic noise disturbance, congestion, and obstruction of view. In order to quantify the negative effects stemming from industrial sites, we estimate – using a hedonic pricing model – the impact of distance to industrial sites on residential property values. We use data on houses sold in the Randstad region and the province of Noord-Brabant (both located in the Netherlands) in the year 2005, together with data on characteristics of a substantial number of industrial sites in the same regions and period. The results reveal that the distance to an industrial site has a statistically significant negative effect on the value of residential properties. However, the effect is largely localized within a relatively short distance from the nearest industrial site. Furthermore, we obtain statistical evidence for substantial localized price differentials, which vary according to the size of an industrial site.
Keywords: O18; R30; R52; 330; industrial sites; negative externalities; hedonic pricing; Wohnstandort; Gewerbegebiet; Externer Effekt; Hedonischer Preisindex; Immobilienpreis; Noord-Brabant (Provinz); Niederlande